BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENYESUAIAN SOSIAL SISWA KELAS IX-E SMP NEGERI 1 WONOASRI KABUPATEN MADIUN - SUHARTI, NINIK (Jurnal Counsellia, 2014)
Changes that occur in the community often felt too fast .As a result, there are people who are able to adjust and compensate for the change and some are not able to adapt itself. For those who are not able to adapt to the changing demands that will have problems in adjustment and social .In the process of social adjustment , students are exposed to the demands and expectations of a very complex and difficult .Many students feel hesitant and less responsive to the situation at hand .As a result of the difficulties to adapt themselves to the environment , eventually students perform actions that violate norms. Found a lot of students who perform inappropriate acts , violate school rules , late entry , ditching , brawl , and others .Group counseling is expected to answer these problems .The results of observations in class IX - E SMP Negeri 1 Wonoasri found some students who have low levels of social adjustment in order to comply with the school that impact on learning outcomes is low.This study uses action research ( Classroom action research ) to class IX - E SMP Negeri 1 Wonoasri with the aim to help students improve their ability in school and social adjustment can adjust to social learning on a regular basis .From the results of this study concluded that group counseling can improve the social adjustment of students effectively, Although there are some students who have not demonstrated a significant improvement or fall into the category of students who no change significantly and there are also students who showed a decline in understanding of themselves , this may be due to the problems it faces more difficult than the problems faced by other friends or because there is no desire in him to improve social adjustment .Keywords : group counseling , social adjustment , action research